DOES ORAL PRESENTATION AFFECT THE DEVELOPMENT OF THE STUDENTS’ ABILITY TO SPEAK IN EFL CLASSROOM? - Ikrar Genidal Riadil (Universitas PGRI Madiun, 2020)
Oral Presentation is one of ways to develop the speaking ability. This study focuses on the impact of oral presentation toward speaking ability based on the student’s point of view in EFL classroom for higher education. The purpose of this study were to investigate the impact of oral presentation to the development of the students ability to speak English and know the student’s difficulties in doing oral presentation in EFL classroom for higher education. From the purpose of this study, the researcher formulates two research problems: (1) What are the impact of oral presentation to the student’s apeaking ability? And (2) What are the factors that make the student difficult to do oral presentation? In this study, the researcher used qualitative research method for collecting data. To obtain the qualitative data, the researcher gave questionnaires for 25 students in the English Department of Tidar University.